Datos sobre la Vitamina D - Linda B. Bobroff; Isabel Valentin-Oquendo (EDIS, 2007)
FCS8640-Span, a 3-page fact sheet by Linda B. Bobroff and Isabel Valentin-Oquendo, is the Spanish version of Facts about Vitamin D (FCS8640). It explains the importance of vitamin D in our diets, how much we need, and how to get this vital nutrient. Published by the UF Department of Family, Youth and Community Sciences, June 2001. Revised April 2006. Translated June 2007.